(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper presents numerical models of a bi-phase, 0.3° full step hybrid stepper motor (HSM), with 16, 24, 32, 40, and, respectively, 48 poles in the stator. For the motor to move with a constant step angle, the stator and the rotor teeth must be shifted against each other with an angle of zero, 90, 180, and 270 electric degrees for each four consecutive stator poles. Due to this, bi-phase steppers with the number of poles in the stator different than eight are hardly seen. Therefore, to allow the construction of HSMs with different numbers of poles, some of the stator poles must be shifted from their symmetrical position. The five topologies’ HSM detent and holding torque characteristics and their geometrical and constructive differences are presented. The Finite Element Method (FEM) based models are developed using the professional software COMSOL Multiphysics.